Potrč v Pleteršnikovem slovarju (Roman Na kmetih, 1954) - Zemljak Jontes, Melita; Valh Lopert, Alenka (Slavia Centralis, 2020)
POTRČ IN PLETERŠNIK’S DICTIONARY (NA KMETIH/THE LAND AND THE FLESH, A NOVEL WRITTEN IN 1954) The article is based upon comparative analysis presenting the vocabulary, written in Potrč’s novel Na kmetih (The Land and the Flesh) (1954), and the entry cues in the Pleteršnik’s Slovensko-nemški slovar (Slovenian-German dictionary) (1894–895). According to the author’s glossary of 89 dialect dictionary entries at the end of the book, the analysis shows that 52 of them have the same dialectal use also in the Pleteršnik’s dictionary.